Analysis of the Application Principle of Horizontal Separation in Jakarta LRT 1B Project: A Legal Review - Situmorang, Urfani Syamuria (Indonesian Journal of Agrarian Law, 2026)
This study elucidates the application of the principle of horizontal separation in land acquisition for the Jakarta LRT Phase 1B Project and how it affects legal certainty for the parties involved. One of the main principles in the Basic Agrarian Law is the principle of horizontal separation, which separates land ownership from objects above and/or below it. The study applied a normative legal research method, employing both statutory and conceptual approaches, supported by an analysis of land acquisition policies for public interests. The outcomes of the study reveal that the application of the principle of horizontal separation applied to the Jakarta LRT Phase 1B project has not been fully consistent. This is especially true when assessing compensation for buildings and utilities standing on state land and land rights. Legal uncertainty and agrarian disputes may arise as a result of this inconsistency. To protect rights and legal certainty, this study uses the strengthening of technical standards for land acquisition that explicitly accommodate the doctrine of horizontal separation.